Implementasi Media Video Berbasis Canva dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam di SMPN 1 Jogoroto - Wati, Mita Widya; Wahyudi, Wahyudi (YASIN, 2025)
This study aims to analyze the implementation of Canva-based video media in improving learning outcomes in Islamic Religious Education (PAI) at SMPN 1 Jogoroto. Video-based learning media help teachers deliver material more effectively, making lessons more engaging and enhancing students’ understanding and motivation. This research employs a qualitative approach with data collection techniques including interviews with teachers and students, as well as classroom observations. The results indicate that the use of Canva-based video media positively impacts PAI learning. Before its implementation, students were generally passive and less enthusiastic about lessons, especially due to the monotonous lecture method. However, after incorporating video media, learning became more interactive, students found it easier to understand the material, and they were more active in discussions and asking questions. Additionally, this media helped teachers create a more comfortable and engaging classroom environment. Despite challenges such as limited electricity access and teachers' readiness to operate digital learning tools, these obstacles can be overcome through school facilities and training programs for educators. Overall, this study confirms that Canva-based video media can be an effective alternative for enhancing learning quality, particularly in Islamic Religious Education.